2012
DOI: 10.4067/s0718-19572012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Digestión secundaria en el análisis del contenido gástrico del calamar rojo Dosidicus gigas (Cephalopoda: Teuthoidea): ¿qué tan importante es?

Abstract: Abstract.-The biological significance of the secondary digestion, i.e., prey of the prey, was determined in the analysis of stomach contents of 112 jumbo squid Dosidicus gigas. Squids were caught on the continental shelf off the coast of centralsouthern Chile during austral winter and spring 2005. All prey (digested and those from opened stomachs of the prey in the squids) found in the squid stomachs were assessed. The results obtained by using several trophic indices (numeric, gravimetric, frequency of occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Few studies have found that D. gigas collected off the Chilean coast do not show feeding differences 1. related to their sexual and ontogenetic condition (Ulloa et al, 2006(Ulloa et al, , 2012Pardo-Gandarillas et al, 2014). Apparently, variability in stomach contents occurs on a seasonal and geographic scale, possibly due to changes in prey availability in the HCS ecosystem (Chong et al, 2005;Pardo-Gandarillas et al, 2014).…”
Section: The Feeding Of the Jumbo Squidmentioning
confidence: 99%
“…Few studies have found that D. gigas collected off the Chilean coast do not show feeding differences 1. related to their sexual and ontogenetic condition (Ulloa et al, 2006(Ulloa et al, , 2012Pardo-Gandarillas et al, 2014). Apparently, variability in stomach contents occurs on a seasonal and geographic scale, possibly due to changes in prey availability in the HCS ecosystem (Chong et al, 2005;Pardo-Gandarillas et al, 2014).…”
Section: The Feeding Of the Jumbo Squidmentioning
confidence: 99%